Risk stratification for hydronephrosis in the evaluation of acute kidney injury: a cross-sectional analysis - Sri Lekha Tummalapalli; John R. Zech; Hyung J. Cho; Celine Goetz (BMJ Open)
Objective To validate an existing clinical decision support tool to risk-stratify patients with acute kidney injury (AKI) for hydronephrosis and compare the risk stratification framework with nephrology consultant recommendations.Setting Cross-sectional study of hospitalised adults with AKI who had a renal ultrasound (RUS) ordered at a large, tertiary, academic medical centre.Participants Two hundred and eighty-one patients were included in the study cohort. Based on the risk stratification framework, 111 (40%), 76 (27%) and 94 (33%) patients were in the high-risk, medium-risk and low-risk groups for hydronephrosis, respectively.Outcomes Outcomes were the presence of unilateral or bilateral hydronephrosis on RUS.Results Thirty-five patients (12%) were found to have hydronephrosis. The high-risk group had 86% sensitivity and 67% specificity for identifying hydronephrosis. A nephrology consult was involved in 168 (60%) patients and RUS was recommended by the nephrology service in 95 (57%) cases. Among patients with a nephrology consultation, 9 (56%) of the 16 total patients with hydronephrosis were recommended to obtain an RUS.Conclusions We further externally validated a risk stratification framework for hydronephrosis. Clinical decision support systems may be useful to supplement clinical judgement in the evaluation of AKI.